2017
DOI: 10.18051/univmed.2017.v36.94-101
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of elicited soybean sprout flour increases calcium level in serum of ovariectomized rats

Abstract: <p>Background<br />The decline in estrogens could lead to an imbalance of bone formation and absorption as well as bone mineralization. Phytoestrogens are known to have the potential to maintain bone health. Calcium and phosphorus are essential components for bone mineralization. This study aimed to investigate the effect of soybean sprout flour consumption on serum calcium and phosphorus levels in ovariectomized rats.</p><p>Methods<br />A randomized post-test-only control group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
0
1
Order By: Relevance
“…The literature suggests that a decrease in plasma calcium level and an increase in phosphorus level in OVX rats with osteoporosis, we observed no change regarding plasma calcium and phosphorus levels in the current study ( Fig. 3 ) ( Elkomy and Elsaid, 2015 ; Aminah et al, 2017 ). It was not clear that why the phosphorus level declined in all experimental animals during the study.…”
Section: Resultscontrasting
confidence: 62%
“…The literature suggests that a decrease in plasma calcium level and an increase in phosphorus level in OVX rats with osteoporosis, we observed no change regarding plasma calcium and phosphorus levels in the current study ( Fig. 3 ) ( Elkomy and Elsaid, 2015 ; Aminah et al, 2017 ). It was not clear that why the phosphorus level declined in all experimental animals during the study.…”
Section: Resultscontrasting
confidence: 62%
“…The ANOVA test results showed that the induction of undernutrition had a significant effect on serum calcium level. The groups A1, A2, and A3 had significantly lower level of serum calcium than the control group (A0), whereas A3 had the lowest level of serum calcium when compared to all the other groups These findings was supported by a previous study conducted by Aminah et al (2017) who concluded that normal level of serum calcium in two months Sprague Dawley rats was 11.36±0.46 mg/dl. In this research, the A1, A2, and A3 had a lower serum calcium as much as 17.08%, 19.45%, and 31.55%, respectively when compared to the control group (A0).…”
Section: Effects Of Milk-based Drink Containing Lactic Acid Bacteria On Serum Calciumsupporting
confidence: 75%